Student attendance management system using RFID - Nurul A'qilah Bt. Hasmizi (School of Microelectronics, University Malaysia Perlis, 2015)
This system is built using open source web-based applications namely MySQL, NetBeans IDE 6.0 and WAMP Server to provide the records and reports for the students attendance. NetBeans IDE 6.0 was used to develop the programming part of the system, MySQL to develop and design the database and PHP is selected as the scripting programming language. This project manage to incorporate the use of passive tags with 125 kHz reader into the system. It is found that the system helps to cut down the time needed to register attendance in a class. This project results as a list of students are recorded by the system through the RFID tag detection.